Proposal for the elaboration of the psychological profile of the Peruvian child - Orellana Méndez, Gaspar (2021)
The article constitutes a theoretical and methodological proposal for the construction of the psychological profile of the Peruvian child. A need that arises after publishing the book on Child Psychology in 1994 and the concern for the spontaneous and recurrent changes in the educational curriculum of initial and primary education in our country. The proposal starts from assuming a dialectical materialist conception of Vygotsky's scientific psychology and cultural historical theory on human and child psychological development. A synthesis of the studies carried out on topics related to the psychology of the Peruvian child from 1940 to 1991 is also presented. It is concluded that this task will be possible with a national research policy on the psychology of the Peruvian child, the implementation of a base of national data of the investigations carried out on the subject and the elaboration of a synthesis of the psychology of the Peruvian child from the studies carried out at least 10 years ago.